Microturbines in dispersed cogeneration - vibroacoustic threats - KICIŃSKI, Jan (Archives of Acoustics, 2007)
The article discusses tendencies in development of turbines, from the macro to micro scale, and their possible application in dispersed cogeneration, i.e. in home power installations. In the small scale, turbines and bearings are a source of specific problems connected with securing stable rotor operation and their susceptibility to some material imperfections, such as shaft cracks. New research tools composing the computer system MESWIR are presented, and results of system stability investigations taking into account thermoelastic deformations of bearing bushes and various variants of their fixing are discussed, along with the results of investigations of the effect of crack depth propagation on the dynamic state of the entire system. The obtained results are rather surprising and frequently in opposition to a so-called engineering intuition. The machine selected for investigations is a three-support rotating machine with two discs, in operation in conditions specific for microturbines (low Sommerfeld numbers). The developed research tools have turned out extremely applicable for assessing vibroacoustic threats generated by this type of machines.